Current Studies in Italian Syntax: Essays Offered to Lorenzo Renzi (Elsevier, 2001)
The book deals with the research currently carried out in Italy on Italian and more generally Romance Syntax.The essays were specially collected to pay homage to Prof. Lorenzo Renzi, a scholar . The book will be of interest ti syntacticians, Romance linguists and students of the Italian Language.